Mekanisme Penjualan Produk Dengan Sistem Konsinyasi Pada Pelaku Usaha Keripik Singkong Di Desa Sendang Agung Bandar Mataram - Dian Cahyana; Nurul Isnaini; Carmidah Carmidah (Pusat Riset dan Inovasi Nasional, 2023)
In Indonesia today many people work as traders. Trading is done to buy and sell, one of which is the sale of consignment or selling point. In this study using field research methods with data collection in the form of interviews with informants. The results of this study indicate that consignment sales were carried out in marketing Mbah Wiji's cassava chips products by entrusting the products to a number of stalls around the production house.